2002
DOI: 10.1042/cs103s202s
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1-induced elevations in purine metabolite concentrations — autoregulatory protection in the canine pericardium?

Abstract: Pericardial fluid accumulates the cardioprotective purine metabolites, as well as the endogenous vasoconstrictor agent endothelin-1 (ET-1). The aim of the present study was to characterize the pericardial concentrations of the purine metabolites adenosine, inosine and hypoxanthine before and after intrapericardial administration of ET-1 to the in situ heart. The closed pericardial sac of anaesthetized dogs (n=9) was cannulated for ET-1 administration and for obtaining native pericardial fluid and control peric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…34 Earlier study has shown that IP administration of ET-1 does not cause transmural ischemia, which was demonstrated by the different alterations of the endocardial and epicardial MAP tracings: significant shortening of the epicardial but not the endocardial MAP duration was observed. 19 Moreover, significant inotropic action of IP INO was not detected in the present study, similarly to the IP application of ET-1. 19 In the present study, only weak cardiovascular effects were observed during IP administration of adenine nucleosides.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…34 Earlier study has shown that IP administration of ET-1 does not cause transmural ischemia, which was demonstrated by the different alterations of the endocardial and epicardial MAP tracings: significant shortening of the epicardial but not the endocardial MAP duration was observed. 19 Moreover, significant inotropic action of IP INO was not detected in the present study, similarly to the IP application of ET-1. 19 In the present study, only weak cardiovascular effects were observed during IP administration of adenine nucleosides.…”
Section: Discussioncontrasting
confidence: 63%
“…19 Moreover, significant inotropic action of IP INO was not detected in the present study, similarly to the IP application of ET-1. 19 In the present study, only weak cardiovascular effects were observed during IP administration of adenine nucleosides. One possible explanation to this finding is that no transmural penetration through the left ventricular wall occurred by the agents' IP administration.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations